Pelatihan Pembuatan Instrumen Penilaian Performance di SD IT An-Nahl Islamic School Pegasing - Sari, Rahmahidayati; Ahmad, Nurul Qomariyah; Nengsi, Ayu Rahma; Nurjani, Nurjani (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
The service that the author does at SDIT An Nahl Islamic School Pegasing is to provide training on making practical assessment instruments to teachers at the school. This training aims to give teachers the skills to make practical assessment instruments. The method that the author uses is CBPR (Community Based Participatory Research). This method is a method that is carried out to connect 2 circles, namely academics and the community by carrying out community service activities according to the needs desired by the community. This method also requires the joint participation of the entire community/society and the involvement of the researcher. From the training that the author provided, teachers who took part in the training felt great benefits from the training and teachers were able to make practice assessment instruments along with the scoring rubric. In addition, the teacher plans to bring the instrument to the school level and discuss it in teacher meetings so that it can be used during the learning process. and do not rule out the possibility that the instrument will be discussed when there are KKG activities.